Clinic Characteristics Are not Associated with the Risk of Healthcare-associated Influenza-like Illness (HA-ILI) Among Young Children in Pediatric Primary Care Settings. (4th October 2017) - Feemster, Kristen; Localio, Russell; Griffis, Heather; Odeniyi, Folasade; Grundmeier, Robert; Coffin, Susan; Metlay, Joshua
Abstract: Background: The majority of pediatric healthcare encounters for influenza-like illness (ILI) take place in ambulatory settings where there may be multiple opportunities for respiratory virus transmission. Recent evidence shows that a prior clinic visit increases the risk of ILI among young children. We hypothesized that clinic factors would be associated with the risk of HA-ILI among children < 6 years old after a primary care encounter. Methods: We conducted a prospective cohort study of a sample of 1308 children presenting to any of the 31 primary care clinics in a large pediatric healthcare network for a non-ILI clinic visit during three consecutive respiratory seasons (2012/13 – 2014/15). HA-ILI cases were defined as any ILI encounter within 8 days after a non-ILI visit. Clinic factors (waiting room patient density or number of ILI encounters at appointment time, time in waiting room, clinic location), sociodemographic and clinical data were obtained electronically and from parent interviews. School attendance (daycare, school or parent) and age (≤2 years and >2 years) were combined to create a 5 category composite variable. Logistic regression models after applying sampling weights evaluated associations between HA-ILI risk and patient age, daycare / school attendance, gender, influenza vaccine receipt and waiting room patient density. Results: Our cohort included 367 HA-ILI cases and 941 non-cases. The majority (48.6%) were ≤2 years and did not attend school, 52.8% were male, and 18.9% received flu vaccine. Mean clinic patient density was 44.2 patients/1, 000 square feet. In multivariable models, only the young age/daycare attendance composite variable was significantly associated with increased HA-ILI risk (OR 2.06, 95% CI 1.48, 2.88). No clinic characteristics were associated with HA-ILI risk and risk did not vary by site. Conclusion: In our cohort of young children, HA-ILI was not associated with the measured clinic characteristics that we hypothesized may increase respiratory virus transmission risk. Instead HA-ILI risk was highest in young daycare attendees who may be more likely to engage in behaviors that increase respiratory virus exposure risk or seek out healthcare services when sick. This suggests that HA-ILI may be more strongly influenced by behavioral factors rather than environmental factors. Disclosures: All authors: No reported disclosures.